Digitalization and AI as Drivers of Change in the Accounting Profession: Opportunities for Innovation and Ethical Issues - Aprida, Aprida; Asmita , Deni Yuli; Lidia, Weni Okta; Nofryanti , Nofryanti (The Future of Education Journal, 2025)
The development of artificial intelligence (AI) technology has brought significant changes to the accounting field, particularly in improving the efficiency, accuracy, and innovation of financial services. The application of AI enables the automation of routine tasks, supports in-depth data analysis, and strengthens strategic decision-making processes. However, the integration of this technology also raises ethical challenges such as data privacy issues, algorithm transparency, and the risk of bias and job losses. This study uses a literature review approach to examine the impact of AI on the accounting profession, including the opportunities and challenges faced. The results indicate that the successful implementation of AI requires enhanced professional competency, the development of ethical and regulatory standards, and cross-stakeholder collaboration to ensure the responsible use of technology. With the right approach, AI can strengthen the position of accountants as strategic partners and drive sustainable growth in the business world.